Der Lerner als virtueller Experte: Ein Game Based Training für die Alphabetisierungs- und Grundbildungsarbeit (W. Bertelsmann Verlag, 2009)
Abstract: From the viewpoint of Akademie Remscheid, a leading provider of further education courses involving education through play, this article presents the facets of the phenomenon of play as relevant to education and illustrates them using several examples of play that can be applied to adult education. The focus is on group games which can be played using simple materials. The central fields of learning targeted by play are identified as social skills, perception, expression, creativity and problem-solving strategies
10.3278/DIE0903W037
Keywords: (thesoz)Erwachsenenbildung; (thesoz)Computerspiel; (thesoz)virtuelle Realität; (thesoz)Analphabetismus; (thesoz)Allgemeinbildung; (thesoz)computerunterstütztes Lernen; Bildungspotenzial; Alphabetisierung; Allgemeinbildung; Spiel; Computerspiel; Lernspiel